Chromosomal radiosensitivity in oncological and non-oncological patients with rheumatoid arthritis and connective tissue diseases - Rzepka, Dinah; Schenker, Hannah; Geinitz, Hans; Silberberger, Elisabeth; Kaudewitz, Dorothee; Schuster, Barbara; Kuhlmann, Lukas; Schonath, Miriam; Ayala Gaona, Horacio; Aschacher, Bernhard; Fietkau, Rainer; Schett, Georg; et al. (Radiation Oncology, 2023)
Background: The risk of developing late radiotoxicity after radiotherapy in patients with high chromosomal radiosensitivity after radiotherapy could potentially be higher compared to the risk in patients with average radiosensitivity. In case of extremely high radiosensitivity, dose reduction may be appropriate. Some rheumatic diseases (RhD), including connective tissue diseases (CTDs) appear to be associated with higher radiosensitivity. The question arises as to whether patients with rheumatoid arthritis (RA) also generally have a higher radiosensitivity and whether certain parameters could indicate clues to high radiosensitivity in RA patients which would then need to be further assessed before radiotherapy. Methods: Radiosensitivity was determined in 136 oncological patients with RhD, 44 of whom were RA patients, and additionally in 34 non-oncological RA patients by three-colour fluorescence in situ hybridization (FiSH), in which lymphocyte chromosomes isolated from peripheral blood are analysed for their chromosomal aberrations of an unirradiated and an with 2 Gy irradiated blood sample. The chromosomal radiosensitivity was determined by the average number of breaks per metaphase. In addition, correlations between certain RA- or RhD-relevant disease parameters or clinical features such as the disease activity score 28 and radiosensitivity were assessed. Results: Some oncological patients with RhD, especially those with connective tissue diseases have significantly higher radiosensitivity compared with oncology patients without RhD. In contrast, the mean radiosensitivity of the oncological patients with RA and other RhD and the non-oncological RA did not differ. 14 of the 44 examined oncological RA-patients (31.8%) had a high radiosensitivity which is defined as ≥ 0.5 breaks per metaphase. No correlation of laboratory parameters with radiosensitivity could be established. Conclusions: It would be recommended to perform radiosensitivity testing in patients with connective tissue diseases in general. We did not find a higher radiosensitivity in RA patients. In the group of RA patients with an oncological disease, a higher percentage of patients showed higher radiosensitivity, although the average radiosensitivity was not high.
CRIS-Team Scopus Importer:2023-06-16
Keywords: Chromosomal aberrations; Collagen vascular disease; Connective tissue disease; Fluorescence in situ hybridisation; Radiation sensitivity; Radiosensitivity; Radiotherapy; Radiotoxicity; Rheumatism; Rheumatoid arthritis

Effective Radiosensitization of HNSCC Cell Lines by DNA-PKcs Inhibitor AZD7648 and PARP Inhibitors Talazoparib and Niraparib - Mentzel, Jacob; Hildebrand, Laura; Kuhlmann, Lukas; Fietkau, Rainer; Distel, Luitpold (International Journal of Molecular Sciences, 2024)
(1) Head and neck squamous cell carcinoma (HNSCC) is common, while treatment is difficult, and mortality is high. Kinase inhibitors are promising to enhance the effects of radiotherapy. We compared the effects of the PARP inhibitors talazoparib and niraparib and that of the DNA-PKcs inhibitor AZD7648, combined with ionizing radiation. (2) Seven HNSCC cell lines, including Cal33, CLS-354, Detroit 562, HSC4, RPMI2650 (HPV-negative), UD-SCC-2 and UM-SCC-47 (HPV-positive), and two healthy fibroblast cell lines, SBLF8 and SBLF9, were studied. Flow cytometry was used to analyze apoptosis and necrosis induction (AnnexinV/7AAD) and cell cycle distribution (Hoechst). Cell inactivation was studied by the colony-forming assay. (3) AZD7648 had the strongest effects, radiosensitizing all HNSCC cell lines, almost always in a supra-additive manner. Talazoparib and niraparib were effective in both HPV-positive cell lines but only consistently in one and two HPV-negative cell lines, respectively. Healthy fibroblasts were not affected by any combined treatment in apoptosis and necrosis induction or G2/M-phase arrest. AZD7648 alone was not toxic to healthy fibroblasts, while the combination with ionizing radiation reduced clonogenicity. (4) In conclusion, talazoparib, niraparib and, most potently, AZD7648 could improve radiation therapy in HNSCC. Healthy fibroblasts tolerated AZD7648 alone extremely well, but irradiation-induced effects might occur. Our results justify in vivo studies.
CRIS-Team Scopus Importer:2024-06-21
Keywords: cell lines; DNA damage response inhibitor; DNA-PK inhibitor; HNSCC; ionizing radiation; kinase inhibitor; PARP inhibitor; radiosensitivity

Ex Vivo Chromosomal Radiosensitivity Testing in Patients with Pathological Germline Variants in Breast Cancer High-Susceptibility Genes BReast CAncer 1 and BReast CAncer 2 - Zuhair Kassem, Tara; Wunderle, Marius; Kuhlmann, Lukas; Rübner, Matthias; Hübner, Hanna; Hoyer, Juliane; Reis, André; Fasching, Peter; Beckmann, Matthias; Hack, Carolin; Fietkau, Rainer; Distel, Luitpold (Current Issues in Molecular Biology, 2023)
Background: Individual radiosensitivity is an important factor in the occurrence of undesirable consequences of radiotherapy. The potential for increased radiosensitivity has been linked to highly penetrant heterozygous mutations in DNA repair genes such as BRCA1 and BRCA2. By studying the chromosomal radiosensitivity of BRCA1/2 mutation carriers compared to the general population, we study whether increased chromosomal radiation sensitivity is observed in patients with BRCA1/2 variants. Methods: Three-color-fluorescence in situ hybridization was performed on ex vivo-irradiated peripheral blood lymphocytes from 64 female patients with a heterozygous germline BRCA1 or BRCA2 mutation. Aberrations in chromosomes #1, #2 and #4 were analyzed. Mean breaks per metaphase (B/M) served as the parameter for chromosomal radiosensitivity. The results were compared with chromosomal radiosensitivity in a cohort of generally healthy individuals and patients with rectal cancer or breast cancer. Results: Patients with BRCA1/2 mutations (n = 64; B/M 0.47) overall showed a significantly higher chromosomal radiosensitivity than general healthy individuals (n = 211; B/M 0.41) and patients with rectal cancer (n = 379; B/M 0.44) and breast cancer (n = 147; B/M 0.45) without proven germline mutations. Chromosomal radiosensitivity varied depending on the locus of the BRCA1/2 mutation. Conclusions: BRCA1/2 mutations result in slightly increased chromosomal sensitivity to radiation. A few individual patients have a marked increase in radiation sensitivity. Therefore, these patients are at a higher risk for adverse therapeutic consequences.
CRIS-Team Scopus Importer:2023-09-08
Keywords: BRCA1; BRCA2; breast cancer; chromosomal radiosensitivity; FISH assay; radiation oncology; radiation sensitivity testing; radiotherapy

FEN1 Inhibition as a Potential Novel Targeted Therapy against Breast Cancer and the Prognostic Relevance of FEN1 - Berfelde, Johanna; Hildebrand, Laura; Kuhlmann, Lukas; Fietkau, Rainer; Distel, Luitpold (International Journal of Molecular Sciences, 2024)
To improve breast cancer treatment and to enable new strategies for therapeutic resistance, therapeutic targets are constantly being studied. Potential targets are proteins of DNA repair and replication and genomic integrity, such as Flap Endonuclease 1 (FEN1). This study investigated the effects of FEN1 inhibitor FEN1-IN-4 in combination with ionizing radiation on cell death, clonogenic survival, the cell cycle, senescence, doubling time, DNA double-strand breaks and micronuclei in breast cancer cells, breast cells and healthy skin fibroblasts. Furthermore, the variation in the baseline FEN1 level and its influence on treatment prognosis was investigated. The cell lines show specific response patterns in the aspects studied and have heterogeneous baseline FEN1 levels. FEN1-IN-4 has cytotoxic, cytostatic and radiosensitizing effects, expressed through increasing cell death by apoptosis and necrosis, G2M share, senescence, double-strand breaks and a reduced survival fraction. Nevertheless, some cells are less affected by the cytotoxicity and fibroblasts show a rather limited response. In vivo, high FEN1 mRNA expression worsens the prognosis of breast cancer patients. Due to the increased expression in breast cancer tissue, FEN1 could represent a new tumor and prognosis marker and FEN1-IN-4 may serve as a new potent agent in personalized medicine and targeted breast cancer therapy.
CRIS-Team Scopus Importer:2024-03-08
Keywords: apoptosis; breast cancer cell lines; FEN1; FEN1 inhibition; FEN1-IN-4; ionizing radiation; necrosis; radiosensitivity; targeted therapy; TNBC

Increased Radiation Sensitivity in Patients with Phelan-McDermid Syndrome - Jesse, Sarah; Kuhlmann, Lukas; Hildebrand, Laura; Magelssen, Henriette; Schmaus, Martina; Timmermann, Beate; Andres, Stephanie; Fietkau, Rainer; Distel, Luitpold (Cells, 2023)
Phelan-McDermid syndrome is an inherited global developmental disorder commonly associated with autism spectrum disorder. Due to a significantly increased radiosensitivity, measured before the start of radiotherapy of a rhabdoid tumor in a child with Phelan-McDermid syndrome, the question arose whether other patients with this syndrome also have increased radiosensitivity. For this purpose, the radiation sensitivity of blood lymphocytes after irradiation with 2Gray was examined using the G0 three-color fluorescence in situ hybridization assay in a cohort of 20 patients with Phelan-McDermid syndrome from blood samples. The results were compared to healthy volunteers, breast cancer patients and rectal cancer patients. Independent of age and gender, all but two patients with Phelan-McDermid syndrome showed significantly increased radiosensitivity, with an average of 0.653 breaks per metaphase. These results correlated neither with the individual genetic findings nor with the individual clinical course, nor with the respective clinical severity of the disease. In our pilot study, we saw a significantly increased radiosensitivity in lymphocytes from patients with Phelan-McDermid syndrome, so pronounced that a dose reduction would be recommended if radiotherapy had to be performed. Ultimately, the question arises as to the interpretation of these data. There does not appear to be an increased risk of tumors in these patients, since tumors are rare overall. The question, therefore, arose as to whether our results could possibly be the basis for processes, such as aging/preaging, or, in this context, neurodegeneration. There are no data on this so far, but this issue should be pursued in further fundamentally based studies in order to better understand the pathophysiology of the syndrome.
CRIS-Team Scopus Importer:2023-03-24
Keywords: atypical teratoid rhabdoid tumor; chromosomal aberrations; Phelan McDermid syndrome; radiation sensitivity; SHANK3 deficiency

Radiosensitivity in individuals with tuberous sclerosis complex - Kuhlmann, Lukas; Stritzelberger, Jenny; Fietkau, Rainer; Distel, Luitpold; Hamer, Hajo (Discover Oncology, 2024)
Benign tumors, but rarely cancer, are common in patients with tuberous sclerosis complex (TSC). Blood samples from patients undergoing treatment for TSC at our institution were analyzed for their individual sensitivity to ionizing radiation. Blood samples were collected from 13 adult patients with TSC. The samples were irradiated ex vivo and analyzed by 3-color fluorescence in situ hybridization. In each patient, aberrations were analyzed in 200 metaphases of chromosomes 1, 2, and 4 and scored as breaks. Radiosensitivity was determined by mean breaks per metaphase (B/M) and compared to both healthy donors and oncologic patients. The radiosensitivity (B/M) of the TSC patient cohort (n = 13; female: 46.2%, B/M: 0.48 ± 0.11) was clearly increased compared to healthy individuals of similar age (n = 90; female: 54.4%; B/M: 0.40 ± 0.09; p = 0.001). There was no difference compared to age-matched oncological patients (n = 78; female: 67.9%; B/M 0.49 ± 0.14; p = 0.246). Similarly, the proportion of radiosensitive (B/M > 0.5) and distinctly radiosensitive individuals (B/M > 0.6) was increased in the TSC and oncological patient cohorts (TSC: 30.8% and 7.7%, oncological patients: 46.2% and 14.1%) compared to the healthy individuals (11.1% and 2.2%). Although patients with TSC develop mostly benign and rarely malignant tumors, they are similarly sensitive to radiation as patients with malignant tumors.
CRIS-Team Scopus Importer:2024-10-18
Keywords: Chromosomal aberrations; In situ hybridization; Ionizing radiation; Radiosensitivity; TSC1; TSC2; Tuberous sclerosis complex

The Effect of Xevinapant Combined with Ionizing Radiation on HNSCC and Normal Tissue Cells and the Impact of Xevinapant on Its Targeted Proteins cIAP1 and XIAP - Fleischmann, Julia; Hildebrand, Laura; Kuhlmann, Lukas; Fietkau, Rainer; Distel, Luitpold (Cells, 2023)
The poor prognosis of HNSCC is partly due to treatment resistance. The SMAC mimetic Xevinapant is a promising new approach to targeted cancer therapy. Xevinapant inhibits cIAP1/2 and XIAP, leading to apoptosis, necroptosis and inhibition of prosurvival signaling. Combining Xevinapant with IR could improve therapeutic potential. The effect of Xevinapant in combination with IR on HNSCC and healthy tissue cells was investigated. Cell growth, cell death, clonogenic survival and DNA double-strand breaks (DSBs) were studied, and intracellular cIAP1 and XIAP levels were evaluated. Xevinapant had cytostatic and cytotoxic, as well as radiosensitizing, effects on the malignant cells, while healthy tissue cells were less affected. Apoptotic and necrotic cell death was particularly affected, but the increase in residual DSBs and the reduced survival implied an additional effect of Xevinapant on DNA damage repair and other cell inactivation mechanisms. cIAP1 and XIAP levels varied for each cell line and were affected by Xevinapant and IR treatment. There was an association between higher IAP levels and increased cell death. Xevinapant appears to be a potent new drug for HNSCC therapy, especially in combination with IR. IAP levels could be an indicator for impaired DNA damage repair and increased susceptibility to cellular stress.
CRIS-Team Scopus Importer:2024-12-16
Keywords: apoptosis; cIAP1/2; head and neck squamous cell carcinoma; inhibitor; interactions; ionizing radiation; targeted therapy; Xevinapant; XIAP